HLA-F on HLA-Null 721.221 Cells Activates Primary NK Cells Expressing the Activating Killer Ig-like Receptor KIR3DS1 - Kiani, Zahra; Dupuy, Franck P; Bruneau, Julie; Lebouché, Bertrand; Zhang, Cindy X; Jackson, Elise; Lisovsky, Irene; da Fonseca, Sandrina; Geraghty, Daniel E; Bernard, Nicole F (The Journal of immunology (1950), 2018)
NK cells elicit important responses against transformed and virally infected cells. Carriage of the gene encoding the activating killer Ig-like receptor KIR3DS1 is associated with slower time to AIDS and protection from HIV infection. Recently, open conformers of the nonclassical MHC class Ib Ag HLA-F were identified as KIR3DS1 ligands. In this study, we investigated whether the interaction of KIR3DS1 on primary NK cells with HLA-F on the HLA-null cell line 721.221 (221) stimulated KIR3DS1+ NK cells. We used a panel of Abs to detect KIR3DS1+CD56dim NK cells that coexpressed the inhibitory NK cell receptors KIR2DL1/L2/L3, 3DL2, NKG2A, and ILT2; the activating NK cell receptors KIR2DS1/S2/S3/S5; and CCL4, IFN-γ, and CD107a functions. We showed that both untreated and acid-pulsed 221 cells induced a similar frequency of KIR3DS1+ cells to secrete CCL4/IFN-γ and express CD107a with a similar intensity. A higher percentage of KIR3DS1+ than KIR3DS1− NK cells responded to 221 cells when either inclusive or exclusive (i.e., coexpressing none of the other inhibitory NK cell receptors and activating NK cell receptors detected by the Ab panel) gating strategies were employed to identify these NK cell populations. Blocking the interaction of HLA-F on 221 cells with KIR3DS1-Fc chimeric protein or anti–HLA-F Abs on exclusively gated KIR3DS1+ cells reduced the frequency of functional cells compared with that of unblocked conditions for stimulated KIR3DS1+ NK cells. Thus, ligation of KIR3DS1 activates primary NK cells for several antiviral functions.